2022
DOI: 10.7554/elife.72638
|View full text |Cite
|
Sign up to set email alerts
|

A novel lineage-tracing mouse model for studying early MmuPV1 infections

Abstract: Human papillomaviruses are DNA viruses that ubiquitously infect humans and have been associated with hyperproliferative lesions. The recently discovered mouse specific papillomavirus (MmuPV1) provides the opportunity to study papillomavirus infections in vivo in the context of a common laboratory mouse model (Mus musculus). To date, a major challenge in the field has been the lack of tools to identify, observe, and characterize individually the papillomavirus hosting cells and also trace the progeny of these c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…We previously validated that the constructed MmuPV1-lox-Cre-lox plasmid can indeed lead to reporter activation, Cre-excision, and MmuPV1 genome recircularization both in vivo and in vitro . 1 However, we previously were not able to observe any wart development at the later time points of the infection with the plasmid and we were also not able to re-infect a second set of mice from the swab samples of the tail skins of the first set of mice (not shown here). These observations indicate to a possibility that the resulting virions in vivo from the generated plasmid might not be generating enough infectious viral particles.…”
Section: Limitationsmentioning
confidence: 60%
See 1 more Smart Citation
“…We previously validated that the constructed MmuPV1-lox-Cre-lox plasmid can indeed lead to reporter activation, Cre-excision, and MmuPV1 genome recircularization both in vivo and in vitro . 1 However, we previously were not able to observe any wart development at the later time points of the infection with the plasmid and we were also not able to re-infect a second set of mice from the swab samples of the tail skins of the first set of mice (not shown here). These observations indicate to a possibility that the resulting virions in vivo from the generated plasmid might not be generating enough infectious viral particles.…”
Section: Limitationsmentioning
confidence: 60%
“…There is a restriction to the availability of lox-Cre-lox plasmid which is a unique reagent generated for this study and is not available commercially. This plasmid can either be generated by following the instructions provided previously elsewhere 1 and briefly mentioned here or can be accessed via contacting to the lead contact listed here.…”
Section: Resource Availabilitymentioning
confidence: 99%
“…Infection with MmuPV1 or oncogenic HPVs leads to increased expression of Ki67, a basal cell proliferation marker [55][56][57][58] and Sundberg et al showed similar staining patterns between Ki67 and K5 in MmuPV1-induced tail tumors [55]. Furthermore, MEK inhibition is known to reduce Ki67 staining in epithelial tumors [59,60].…”
Section: Mek Inhibitor Effects On Tissue Morphology and Cellular Biom...mentioning
confidence: 98%
“…Importantly, the tractability of a murine model offers an approach to lineage tracing of MmuPV1 infected cells, including observation of late events and spatial analysis of host-pathogen interactions, which could transform our understanding of HPV late gene expression. 189 Therapeutic strategies against HPV infection would involve inhibiting the viral life cycle and, for high-risk types, targeting persistent infection by interfering with increased viral oncoproteins expression responsible for cancer progression. 190 A strategy to reveal HPV infection in the lower epithelial layers would involve induction of capsid protein synthesis as this would stimulate an immune response against infection.…”
Section: Future Directionsmentioning
confidence: 99%
“…However, murine epithelia generally display fewer cell layers than human epithelia 188 and MmuPV1 does not express an E5 protein, which is important for late gene expression 44,45 meaning that late events in the MmuPV1 184 life cycle may exhibit significant differences to that of HPVs. Importantly, the tractability of a murine model offers an approach to lineage tracing of MmuPV1 infected cells, including observation of late events and spatial analysis of host‐pathogen interactions, which could transform our understanding of HPV late gene expression 189 …”
Section: Introductionmentioning
confidence: 99%